MEMBANGUN INTEGRASI ILMU-ILMU SOSIAL DAN HADIS NABI - Benny Afwadzi (Jurnal Living Hadis, 2016)
This article attempt to discuss the accommodation of social sciences into the study of Prophetic traditions (hadith) as part of the integration of science and religion. In this integration process, hadith takes a role as material object and benefit formal object from a wide range of social sciences, such as sociology, anthropology, geography, history, economics, psychology, as well political science. Thus, social sciences may in part help the practice of Hadith to formulate more contextual meaning that has been applied in various times and places. Take an instance,the contextual meaning of ”Quraisy” with people who have influence, gain fanatical support, and have the capability and quality in holding the position as head of state.